International conference on nonlinear science and complexity NSC 2025 : abstract book - Leonel, Edson Denis [UNESP]; Macau, Elbert Einstein Nehrer (IGCE, 2025)
This conference provided a forum for the exchange of recent developments, discoveries, and advances in Nonlinear Dynamics and Complexity. It presented fundamental and frontier theories and techniques relevant to modern science and technology, stimulated further research interest in the exploration of nonlinear science and complexity, and directly conveyed new knowledge to young researchers, engineers, and technologists working in related fields.

Esta conferência proporcionou um fórum para a troca de desenvolvimentos, descobertas e avanços recentes em Dinâmica Não Linear e Complexidade. Apresentou teorias e técnicas fundamentais e de vanguarda relevantes para a ciência e tecnologia modernas, estimulou o interesse em pesquisas adicionais na exploração da ciência não linear e da complexidade e transmitiu diretamente novos conhecimentos a jovens pesquisadores, engenheiros e tecnólogos que atuam em áreas afins.
Keywords: Sistemas dinâmicos; Sistemas complexos; Dinâmica não- linear; Física estatística; Dynamic systems; Complex systems; Nonlinear dynamics; Statistical physics